Tinjauan Fiqh Siyasah Pada Pengisian Kekosongan Jabatan Kepala Daerah oleh Wakil Kepala Daerah - Ghafar, Taufik; Firmansyah, Heri (Universitas Ekasakti, 2023)
This research discusses the causes of vacancies in regional head positions by deputy regional heads in Indonesia and the urgency of filling them, especially if the remaining term of office is more than 18 months. Using descriptive qualitative methods and Law Number 10 of 2016 as primary legal material, the research found that legal uncertainty regarding the time limit for filling this position often hampers the replacement process. In regional government theory, the positions of regional heads and their deputies are very important and inseparable, considering their roles in regional management and leadership. From Dusturiyah's siyasah review, the replacement of regional heads by their deputies is not only permitted but also mandatory, considering that both of them were elected together with the same vision and mission. The role of the deputy regional head is important for the benefit of the people, namely in providing considerations, input and carrying out the duties of the regional head, as well as the need to immediately fill this vacancy and emphasize the need for legal clarity to immediately fill the position.